Postmortem Toxicology of Tadalafil in a Forensic Case - Maria Laura Schirripa; Letizia Gnetti; Edda Emanuela Guareschi (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Tadalafil is an inhibitor of the enzyme human cyclic guanosine monophosphate–specific phosphodiesterase, type 5 (PDE-5). A mild vasodilator, it is primarily used for the treatment of erectile dysfunction (ED), an increasingly common condition. Other clinical uses include benign prostatic hyperplasia and pulmonary arterial hypertension. Adverse events are rare. Absolute contraindications include serious cardiac disease. Despite the widespread use of tadalafil, very little is known about any associations with lethal cases in forensic pathology, with related post-mortem redistribution phenomena and toxicology. This study presents a forensic case with possible contribution of tadalafil to the cause of death. Furthermore, an overview of tadalafil and a discussion on its relevance in the forensic practice are discussed. The administration of tadalafil might act as a concurrent cause, or contributing factor, to lethal cardiogenic shock in subjects with cardiac disease.